The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found